The β‐catenin pathway contributes to the effects of leptin on SREBP‐1c expression in rat hepatic stellate cells and liver fibrosis. (12th April 2013) - Zhai, Xuguang; Yan, Kunfeng; Fan, Jiye; Niu, Minghui; Zhou, Qian; Zhou, Yan; Chen, Hongshan; Zhou, Yajun
<x xml:space="preserve">Abstract</x> Background and Purpose Liver fibrosis is commonly associated with obesity and most obese patients develop hyperleptinaemia. The adipocytokine leptin has a unique role in the development of liver fibrosis. Activation of hepatic stellate cells (HSCs) is a key step in hepatic fibrogenesis and sterol regulatory element‐binding protein‐1c (SREBP‐1c) can inhibit HSC activation. We have shown that leptin strongly inhibits SREBP‐1c expression in rat HSCs. Hence, we aimed to clarify whether the β‐catenin pathway, the crucial negative regulator of adipocyte differentiation, mediates the effects of leptin on SREBP‐1c expression in HSCs and in mouse liver fibrosis. Experimental Approach HSCs were prepared from rats and mice. Gene expressions were analysed by real‐time PCR, Western blot analysis, immunostaining and transient transfection assays. Key Results Leptin increased β‐catenin protein but not mRNA levels in cultured HSCs. Leptin induced phosphorylation of glycogen synthase kinase‐3β at Ser9 and subsequent stabilization of β‐catenin protein was mediated, at least in part, by ERK and p38 MAPK pathways. The leptin‐induced β‐catenin pathway reduced SREBP‐1c expression and activity but did not affect protein levels of key regulators controlling SREBP‐1c activity, and was not involved in leptin inhibition of liver X receptor α. In a mouse model of liver injury, the β‐catenin pathway was shown to be involved in leptin‐induced liver fibrosis. Conclusions and Implications The β‐catenin pathway contributes to leptin regulation of SREBP‐1c expression in HSCs and leptin‐induced liver fibrosis in mice. These results have potential implications for clarifying the mechanisms of liver fibrogenesis associated with elevated leptin levels.